Planification de l’espace maritime et approche écosystémique en contexte transfrontalier : illustration franco-belge - Betty Queffelec (VertigO)
Theoretically, ecosystem approach implies a transboundary coordination of marine and coastal zones. However, Maritime Spatial Planning, which has been drawn as a way to operationnalize it, remains mainly implemented at national level and without real coordination. The french-belgian case shows it. But, European Law could lead to an evolvement. It is one of the objectives of the Directive proposal to establish a framework for maritime spatial planning and integrated coastal management.